Fabrication, drug delivery kinetics and cell viability assay of PLGA-coated vancomycin-loaded silicate porous microspheres. Issue 1 (1st January 2022) - Zirak, N.; Maadani, A.M.; Salahinejad, E.; Abbasnezhad, N.; Shirinbayan, M.
Abstract: Porous ceramic microspheres are a desirable substance for bone tissue reconstruction and delivery applications. This study focuses on Mg–Ca silicate microspheres encapsulated in biodegradable poly (lactic-co-glycolic acid) (PLGA) to serve as a biocompatible carrier for the controlled release of vancomycin hydrochloride. In this regard, diopside (MgCaSi2 O6 ), bredigite (MgCa7 Si4 O16 ), and akermanite (MgCa2 Si2 O7 ) powders were synthesized by sol-gel and subsequent calcination methods. Then, porous akermanite, diopside and bredigite microspheres of 700–1000 μm in diameter were fabricated by using carbon porogen, droplet extrusion and sintering, then loaded with the drug and eventually coated with PLGA. The bare microspheres showed a considerable burst release mode of the drug into a physiological medium, whereas PLGA coating of the microspheres reduced the burst release level. To investigate effective mechanisms governing in the drug release from the carriers, the contribution of burst, degradation, and diffusion was analyzed by the sequential quadratic programming algorithm method. It was found that the relative contribution of diffusion to bioresorption is ranked as diopside > akermanite > bredigite, whereas PLGA coating dominates the diffusion mechanism. The dental pulp stem cells cytocompatibility MTT assay of the microspheres also showed that the drug loading deteriorates but PLGA coating improves the cell biocompatibility significantly. Comparatively, the biocompatibility of the PLGA-coated microspheres was ranked as akermanite > diopside > bredigite, as a result of a compromise between the release of the constituting ions of the ceramic carriers and vancomycin molecules. It was eventually concluded that PLGA-coated Mg–Ca silicate microspheres are promising candidates for drug-delivery bone tissue engineering and dental bone grafting applications.